Growth decline in European beech associated with temperature-driven increase in reproductive allocation - Andrew Hacket-Pain; Jakub Szymkowiak; Valentin Journé; Maciej K. Barczyk; Peter A. Thomas; Jonathan G. A. Lageard; Dave Kelly; Michał Bogdziewicz (Proceedings of the National Academy of Sciences, 2025)
Climate change is impacting forests in complex ways, with indirect effects arising from interactions between tree growth and reproduction often overlooked. Our 43-y study of European beech ( Fagus sylvatica ) showed that rising summer temperatures since 2005 have led to more frequent seed production events. This shift increases reproductive effort but depletes the trees’ stored resources due to insufficient recovery periods between seed crops. Consequently, annual tree ring increments have declined by 28%, dropping from a stable average of 1.60 mm y −1 between 1980 and 2005 to 1.16 mm y −1 thereafter. Importantly, this growth decline occurred without an accompanying trend in summer drought, indicating that altered reproductive patterns—not moisture stress—are driving the reduction. This creates a “perfect storm”: Increased reproductive effort drains resources, viable seed output falls due to the loss of mast-seeding benefits via pollination and lower seed predation, and the ongoing growth decline reduces current carbon uptake and future reproductive potential. These compounding factors threaten the sustainability of Europe’s most widespread forest tree. Our findings unveil a critical yet underrecognized indirect mechanism by which climate change endangers forest ecosystems, emphasizing the need to consider interactions between demographic processes when assessing species vulnerability to climate change.